Small and Medium Enterprise Development: Concept Overview of Stakeholder Engagement, Business Coaching, and the ADDIE Model in Training - Irianto, Jusuf (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2022)
There are various problems faced by Small and Medium Enterprises (SMEs), especially those related to business competition, technological developments, and transformation into the digital era. These various problems require the strategic role of the government and other stakeholders to be present to provide solutions. The ability of SME entrepreneurs can be developed through various forms of intervention, both in the form of mentoring and training. This study is intended to describe the concept of stakeholder involvement, assistance in the form of business coaching, and training programs using the ADDIE system model. There needs to be empirical research on government institutions that function to foster and develop SMEs in various forms, for example through business incubators or other formats